HEMERA 1 CarboxyHEMoglobin oxygEn delivery for Revascularization in Acute Stroke: A Prospective, Randomized Phase 1 Clinical Trial - Italo Linfante; Wayne Clark; Diogo C. Haussen; Ricardo Hanel; Rwoof Reshi; Guilherme Dabus; Ronald Jubin; Mona P. Roshan; Star Belnap; Thanh N. Nguyen; James Grotta; Robert Wicks; et al. (Stroke: Vascular and Interventional Neurology)
Background PP‐007 is a polyethylene glycol (PEG)ylated bovine carboxyhemoglobin gas transfer molecule with pleotropic cytoprotective effects, vasodilatation, plasma expansion, and optimization of oxygen delivery. Rodent middle cerebral artery occlusion models have demonstrated that PP‐007 increases blood flow in the collateral circulation and reduces final infarct volumes, supporting a potential role as neuroprotective agent in acute ischemic stroke. We aim to evaluate the safety and feasibility of PP‐007 as an adjunctive treatment to mechanical thrombectomy (MT) in patients with stroke secondary to large vessel occlusion. Methods HEMERA‐1 (CarboxyHEMoglobin OxygEn delivery for Revascularization in Acute Stroke) was a multicenter, prospective, randomized, controlled phase 1 clinical trial. Anterior circulation large vessel occlusion patients were assigned in a 3:1 ratio to receive either PP‐007 (320 mg/kg: 30 min bolus followed by 2‐h infusion) plus MT or MT alone within 24 hours after symptom onset. Comprehensive safety evaluation was performed by independent Data Monitoring Safety Board and Imaging Core Lab. Results From October 1, 2021 to June 30, 2022, a total of 17 patients were recruited. Age, baseline National Institutes of Health Stroke Scale score, and Alberta Stroke Program Early CT Score were 74.8±12.7 years, 17.3±4.2, and 7.9±1.8, respectively. Twelve patients were randomized to PP‐007 plus MT, 1 was randomized but not treated, 4 patients were randomized to MT alone. Recanalization of the occluded vessel was achieved in all patients. A transient systolic blood pressure increase (20–40 mm Hg) during the bolus was observed in all PP‐007 patients without any clinical consequences. There were no other safety concerns. Conclusion No significant safety concerns were identified for the adjunctive use of PP‐007 in patients undergoing MT. (The study was funded by Prolong Pharmaceuticals. Registration URL: https://www.clinicaltrials.gov; Unique identifier: NCT04677777.